Differential Silica Nanoparticles Functionalized with Branched Poly(1-Vinyl-1,2,4-Triazole): Antibacterial, Antifungal, and Cytotoxic Qualities - Kaptan Usul, Sedef; Lüleci, Hatice Büşra; Değirmenci, Nurdan Sena; Ergüden, Bengu; Soydan, Ali Murat; Aslan, Ayşe (Hindawi Limited, 2024)
This research aims to improve antimicrobial materials based on functional silica nanoparticles. Three different methods were used in the study to create silica nanoparticles with other properties. The nanoparticles' morphological structures are porous, hollow, and filled with spherical forms. The surface of these nanoparticles was grafted with poly(1-vinyl-1,2,4-triazole) (PVTri). The morphological properties of nanocomposites were used for analysis. In contrast, thermal gravimetric analysis was used to characterize the thermal properties of nanocomposites (thermogravimetric analysis). The silica nanoparticles were evaluated for their in vitro antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Saccharomyces cerevisiae using minimum inhibitory concentration measurement. Silica nanoparticles have different antifungal and antibacterial properties related to their structure. The cytotoxic effects of the silica nanoparticles on HaCaT cells were performed with an MTS assay. In this study, we observed that high doses of HSS and e-SiO2 decreased cell growth, while HSS and e-SiO2 composite with PVTri increased cell proliferation. © 2024 Elsevier B.V., All rights reserved.
Keywords: Cell proliferation; Escherichia coli; Nanocomposites; SiO2 nanoparticles; Thermogravimetric analysis; Yeast; Antibacterials; Antifungals; Antimicrobial materials; Cytotoxic; Functionalized; Material-based; Morphological properties; Morphological structures; Other properties; Silica nanoparticles